359 Intrasubject Variation in Estimates of Neonatal Intrahepatocellular Lipid using 1H Nmr Spectroscopy. (October 2012) - Murphy, A; Adams, VL; Hill, H; Morgan, C; Kemp, GJ; Abernethy, LJ; Turner, MA
Abstract : Background and Aims: To date there are no reports of intra-subject variability for intrahepatocellular lipid (IHCL) assessed using 1H NMR spectroscopy in neonates. This study utilized a high-field (3-Tesla) MRI scanner to perform repeated assessment of IHCL on neonates. Methods: Measurements were acquired using a 10 x 10 x 10 mm voxel during 90 seconds. IHCL was assessed using the ratio between the lipid and water peaks. The within subject coefficient of variation (WS CV) was calculated. Results: In 15 babies, MRS was measured twice in each lobe in the same region of interest. Values > 0.2 gave reproducible results; the WS CV was 12% on the right and 3% on the left. MRS was measured once in each lobe in 32 babies (GA at birth median 36 weeks, range 24–42; GA at scan median 42 weeks, range 37–46). Among 17 babies with MRS > 0.2 on both sides WS CV calculated between left and right for was 54% (95% CI 50%–58%) and Mean (SD) was 0.73 (0.33) on the right and 0.58 (0.42) on the left (p<0.005). Conclusions: Neonatal IHCL measured using 3T is markedly lower than other age groups and systematically higher on the right than the left possibly reflecting the influence of lobe size and cardiac pulsation. Values ≤ 0.2 are imprecise and should be classified as below the limit of quantification. The optimal imaging strategy is likely to use a consistent region of interest within the right lobe.